Myoglobin facilitates angiotensin II-induced constriction of renal afferent arterioles - Liu, Zhi Zhao; Schubert, Rudolf (American journal of physiology. Renal physiology, 2017)
Vasoconstriction plays an important role in the development of acute kidney injury in rhabdomyolysis. We hypothesized that myoglobin enhances the angiotensin II (ANG II) response in afferent arterioles by increasing superoxide and reducing nitric oxide (NO) bioavailability. Afferent arterioles of C57Bl6 mice were isolated perfused, and vasoreactivity was analyzed using video microscopy. NO bioavailability, superoxide concentration in the vessel wall, and changes in cytosolic calcium were measured using fluorescence techniques. Myoglobin treatment (10−5 M) did not change the basal arteriolar diameter during a 20-min period compared with control conditions. NG-nitro-l-arginine methyl ester (l-NAME, 10−4 M) and l-NAME + myoglobin reduced diameters to 94.7 and 97.9% of the initial diameter, respectively. Myoglobin or l-NAME enhanced the ANG II-induced constriction of arterioles compared with control (36.6 and 34.2%, respectively, vs. 65.9%). Norepinephrine responses were not influenced by myoglobin. Combined application of myoglobin and l-NAME further facilitated the ANG II response (7.0%). Myoglobin or l-NAME decreased the NO-related fluorescence in arterioles similarly. Myoglobin enhanced the superoxide-related fluorescence, and tempol prevented this enhancement. Tempol also partly prevented the myoglobin effect on the ANG II response. Myoglobin increased the fura 2 fluorescence ratio (cytosolic calcium) during ANG II application (10−12 to 10−6 M). The results suggest that the enhanced afferent arteriolar reactivity to ANG II is mainly due to a myoglobin-induced increase in superoxide and associated reduction in the NO bioavailability. Signaling pathways for the augmented ANG II response include enhanced cytosolic calcium transients. In conclusion, myoglobin may contribute to the afferent arteriolar vasoconstriction in this rhabdomyolysis model.
First published January 4, 2017
Gesehen am 24.10.2018